The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/2032093
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Acupuncture and Rehabilitation Training on Limb Movement and Living Ability of Patients with Hemiplegia after Stroke

Abstract: Stroke is a disease with a high disability rate, having a serious impact on that patient’s working and daily survival quality and bringing economic burden to the family and society. Patients with stroke hemiplegia are mostly tetraplegic and have difficulty regulating their balance, and their long-term symmetry has been destroyed. The application in the rehabilitation process of acupuncture in patients with hemorrhagic stroke may produce unexpected effects. It is very effective to study the effect of acupunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Yang [21] et al randomly divided 112 patients with acute ischemic stroke into two groups, the control group was routinely rehabilitated, the observation group was treated with acupuncture for 15 days, and the Fugl-Meyer and ADL scores of the observation group after treatment were higher than those of the control group, and the overall effective rate of the control group was high. Huang [22] assigned 50 cases of acute ischemic stroke patients who had been rehabilitated with acupuncture as the observation group, and 50 cases of acute ischemic stroke who have undergone drug treatment as the control group. The observation group underwent acupuncture at the philtrum, Triple Yin Intersection, Inner Pass, Fenglong acupoint, Taichong acupoint, Chize acupoint, Zu Sanli, and many more, the treatment was done over the course of 6 weeks.…”
Section: Acupuncture Combined Rehabilitationmentioning
confidence: 99%
“…Yang [21] et al randomly divided 112 patients with acute ischemic stroke into two groups, the control group was routinely rehabilitated, the observation group was treated with acupuncture for 15 days, and the Fugl-Meyer and ADL scores of the observation group after treatment were higher than those of the control group, and the overall effective rate of the control group was high. Huang [22] assigned 50 cases of acute ischemic stroke patients who had been rehabilitated with acupuncture as the observation group, and 50 cases of acute ischemic stroke who have undergone drug treatment as the control group. The observation group underwent acupuncture at the philtrum, Triple Yin Intersection, Inner Pass, Fenglong acupoint, Taichong acupoint, Chize acupoint, Zu Sanli, and many more, the treatment was done over the course of 6 weeks.…”
Section: Acupuncture Combined Rehabilitationmentioning
confidence: 99%
“…Recent evidence suggests that acupuncture can be effective in treating cerebrovascular disease 17 18. The WHO has proposed that stroke and its sequelae are the main indications for acupuncture 19.…”
Section: Introductionmentioning
confidence: 99%
“…There are systematic reviews conducted recently suggested that acupuncture therapy is effective and safe for patients with flaccid and spastic hemiplegia after stroke based on conventional gait assessment tools 20 21. Randomised controlled trials (RCTs) found that acupuncture improved the balance and lower limb motor function of patients with hemiplegia after stroke 17 22 23. A study of 134 subacute phase stroke participants compared acupuncture plus conventional treatment with conventional treatment only, with 24 sessions of acupuncture therapies and 3-month follow-up, and the result revealed that acupuncture may promote motor function recovery mainly by enhancing the lower limb ability and diminishing the compensation strategies earlier to correct the abnormal gait pattern 24…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the architecture of the whole-brain functional network was altered after acupuncture in healthy subjects, and the alterations certified the specificity of acupoints (Han et al, 2020). The clinical applicability and efficacy of acupuncture in rehabilitation after stroke has been demonstrated in several studies (Lv et al, 2021;Zhang et al, 2022). The Zusanli (ST36) and Quchi (LI11) acupoints are the most commonly used acupoints for the treatment of stroke (Xie et al, 2013;Liu et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%